IKLAN SEBAGAI PROGRAM KOMUNIKASI PEMASARAN (STUDI PADA BTS MEAL MCDONALDS) - Aslikhatul Ummah Sofi Alif (Nusantara Hasana Journal, 2023)
McDonalds took the right step in conducting marketing communications by collaborating with the worldfamous K-Pop boy band BTS to launch the BTS Meal product. As for advertising as a marketing communication program, namely through 4 stages including Advertising, Personal Selling, Sales Promotion and Public Relations and Publicity. The type of research in the preparation of this article is a type of library research, namely the process of systematically identifying the discovery and analysis of documents that contain information related to research problems in the sense of making the library the basis of the main (primary) data source. The results of the first study, McDonalds as the largest fastfood restaurant advertises BTS through various media. Second, face-to-face sales can take place by purchasing the BTS Meal package menu via McDonalds delivery or ordering directly via Drive Thru vehicles, be it bicycles, motorbikes to cars or via delivery partners. on line. The three sales promotions held by McDonalds are to increase rapidly through 3 stages of the BTS Meal package menu, selling special BTS merchandise items through the Weverse application and providing exclusive content through the McDonalds application. Fourth, the good relationship between the Indonesian people and BTS as one of the countries with the most ARMY fans in the world. The publicity by McDonalds also contributed to supporting BTS as the most successful global brand of all time.